2020
DOI: 10.1109/access.2020.3041767
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Stage U-Shape Convolutional Network for Esophageal Tissue Segmentation in OCT Images

Abstract: Automatic segmentation is the crucial step for esophageal optical coherence tomography (OCT) image processing, which is able to highlight diagnosis-related tissue layers and provide characteristics such as shape and thickness for esophageal disease diagnosis. This study proposes a dual-stage framework using a specifically designed encoder-decoder network configuration for accurate and reliable esophageal layer segmentation, which is named as the dual-stage U-shape convolutional network (D-UCN). The proposed ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…However, smaller sample sizes can sometimes result in higher accuracy, which has been observed in the reviewed studies (26,32). Interestingly, studies that reported the highest accuracy did not provide information on the sample size used, which suggests that other factors such as feature processing and model parameter tuning may also play a crucial role (29,37,55). Therefore, future studies should aim to investigate the optimal sample size for issues related to the clinical eld, while also examining the characteristics of ML algorithms, including feature extraction, selection, and optimization, to achieve more accurate and reliable results.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, smaller sample sizes can sometimes result in higher accuracy, which has been observed in the reviewed studies (26,32). Interestingly, studies that reported the highest accuracy did not provide information on the sample size used, which suggests that other factors such as feature processing and model parameter tuning may also play a crucial role (29,37,55). Therefore, future studies should aim to investigate the optimal sample size for issues related to the clinical eld, while also examining the characteristics of ML algorithms, including feature extraction, selection, and optimization, to achieve more accurate and reliable results.…”
Section: Discussionmentioning
confidence: 89%
“…In one case, an average accuracy of 98% was achieved using Optical coherence tomography (OCT) images (Fig. 5) (37).…”
Section: Ec Image Segmentationmentioning
confidence: 99%
“…In one case, an average accuracy of 98% was achieved using Optical coherence tomography (OCT) images (Fig. 5 ) [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Faster R-CNN (6445 images), SegNet (6473 images), Neuro_T (5162 images), and YOLO v5 (4447 images) were other ML algorithms that utilized a large sample size for training, testing, and validation [ 24 , 27 , 42 , 49 ]. In addition, in studies focused on early detection of esophageal cancer, U-Net [ 33 , 35 , 36 , 38 , 39 ], Faster R-CNN [ 13 , 26 , 48 , 49 , 51 ] SSD [ 13 , 20 , 25 , 30 , 37 ] algorithms reported in 5 studies had the highest number of uses among all ML algorithms. VGG16 algorithm was also used in 3 studies [ 25 , 28 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation